SELF MANAGEMENT PROGRAMS ON THE QUALITY OF LIFE OF CHILDREN AND ADOLESCENTS WITH CHRONIC KIDNEY DISEASE: A SYSTEMATIC REVIEW - Syarifah Aini Tanjung; Nur Agustini; Dessie Wanda (Jurnal Ipteks Terapan, 2023)
Introduction : Diagnosis of disease Serious like disease kidney chronic disease (CKD) have implications in many field life children and their families , and can dramatically affect quality their life . One program to improve quality life is by involving self- management monitoring conditions , compliance to treatment and response to sustain quality live . Method : review systematically , started with formulate PICO: In patients children and adolescents , whether program management self compared to with intervention standard can influence quality live . Furthermore do search literature from databases ProQuest, ScienceDirect, Scopus, EBSCOhost, PubMed, ClinicalKey , ClinicalKey Nursing, Sage Journal and Google Scholar . Criteria inclusion is related research articles self-management child with disease kidney chronic , not review article , in English, research conducted on children and adolescents , and there are version full text . Results : Total articles obtained beginning from the entire database is totaled 106,740 articles , once done screening according to criteria inclusion , obtained 9 articles with various type research design . Eight from nine studies show There is the effect of self-management programs on pediatric and adolescent patients with CKD. Self-management program in adolescents with disease kidney Chronic can be education or training , peer support or group base care as well as preparation in terms of transition service health to services mature . Conclusion: Self-management program for children and adolescents effectiveness can improve results health , slow down development disease and delaying replacement therapy kidneys ( dialysis ), however self-management is complex and requires support multidisciplinary